Determining the coordinates of the earthquake hypocenter with the simultaneous determination of seismic wave velocities - Sidorkina, Yu. A.; Aslanov, T. G. (Vestnik Dagestanskogo gosudarstvennogo tehničeskogo universiteta. Tehničeskie nauki (Online), 2022)
Objective . The purpose of the study is to determine the coordinates of the earthquake hypocenter with the simultaneous determination of the seismic wave velocity. Method . The study is based on the use of figures of the fourth and second order - the Cassini oval and hyperbola, figures of the second order - ellipse and hyperbola and combined methods that allow, at given seismic wave velocities, according to three seismic sensors, to determine the coordinates of the earthquake hypocenter. In this case, the velocities are assumed to be known a priori. According to the readings of the fourth seismic sensor, and for given seismic wave velocities, the distance from the fourth seismic sensor to the hypocenter is determined. Again, according to the coordinates of the fourth seismic sensor and the hypocenter coordinates calculated from the three seismic sensors, the distance between them is calculated. If the seismic wave velocities do not correspond to the true ones, a discrepancy will appear between the two calculated values of the distances from the hypocenter to the fourth seismic sensor. By varying the velocities of seismic waves when calculating the coordinates of the hypocenter, we achieve a minimum discrepancy. Result . The problem of determining the coordinates of the earthquake hypocenter with the simultaneous determination of seismic wave velocities is solved. The error distribution densities in determining the coordinates of the earthquake hypocenter and seismic wave velocities are obtained. Conclusion . The proposed method makes it possible to increase the accuracy of determining the coordinates of the earthquake source, as well as to refine the values of seismic wave velocities.